Post a New Question

Math

posted by on .

I can't figure our how they got the answer to this question:

Use the following function to find f(-2)? f(x)=x(squared)-3

This is how I am solving the problem:
f(x)=x(squared) -3
f(-2)=(-2)squared -3
f(-2)=4-3
f(-2)=1

The correct answer is 2 and I don;t know why.

  • Math - ,

    You are right, the answer is 1

    You should have enough faith and trust in your own math ability to say "the book is wrong" on this one.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question